STUDI KEPUTUSAN PETANI LADA PUTIH TERHADAP PENGGUNAAN JUNJUNG HIDUP DALAM SISTEM PERTANIAN BERKELANJUTAN - Paramitha, Annisa Pradnya; Mustikarini, Eries Dyah; Khodijah, Nyayu Siti (Enviagro: Jurnal Pertanian dan Lingkungan, 2023)
White pepper is a superior spice plant from the agricultural sector in Bangka Belitung Islands Province which is known in the world market as Muntok White Pepper with uniqueness that comes from Geographical Indications (GI). The high production of Muntok White Pepper in Bangka Belitung Islands Province does not provide benefit for farmers, because farmers have to pay for the procurement of large production inputs with a relatively short production time. This problem needs to be addressed by farmers through the application of sustainable farming system with Good Agriculture Practice (GAP) such as the live climbing pole using. The farmer's decision to change the dead climbing pole to the live climbing pole is influenced by several factors. The purpose of this research was to analyze the determinant of white pepper farmers’s decision on the live climbing pole using. This research was conducted in Air Gegas Sub-district, South Bangka District on August until December 2022. The data used on this research was secondary data collected through library research method. The results of this research indicate that the decision of white pepper farmers on the live climbing pole using is influenced by six factors, including age, level of formal education, farming experience, land area, land ownership status, and participation on agricultural group.